Early postnatal interactions between beige adipocytes and sympathetic neurites regulate innervation of subcutaneous fat - Jingyi Chi; Zeran Lin; William Barr; Audrey Crane; Xiphias Ge Zhu; Paul Cohen (eLife, 2021)
While beige adipocytes have been found to associate with dense sympathetic neurites in mouse inguinal subcutaneous white fat (iWAT), little is known about when and how this patterning is established. Here, we applied whole-tissue imaging to examine the development of sympathetic innervation in iWAT. We found that parenchymal neurites actively grow between postnatal day 6 (P6) and P28, overlapping with early postnatal beige adipogenesis. Constitutive deletion of Prdm16 in adipocytes led to a significant reduction in early postnatal beige adipocytes and sympathetic density within this window. Using an inducible, adipocyte-specific Prdm16 knockout model, we found that Prdm16 is required for guiding sympathetic growth during early development. Deleting Prdm16 in adult animals, however, did not affect sympathetic structure in iWAT. Together, these findings highlight that beige adipocyte-sympathetic neurite communication is crucial to establish sympathetic structure during the early postnatal period but may be dispensable for its maintenance in mature animals.